The native races of the Pacific states of North America. [electronic resource] - Bancroft, Hubert Howe, 1832-1918. (New York : D. Appleton, 1875)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 14099-14104. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44